Meningkatkan Keterampilan Membaca Pemahaman Siswa Kelas III SD melalui Metode Drill dalam Pembelajaran Bahasa Indonesia - Nindya Arrohmah; Ibnu Muthi (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This study aims to explain the application of the drill method and to analyze the improvement of students' ability to understand initiation after using this method. This study uses the Action Research (CAR) method in the classroom. This study was conducted in two cycles, each consisting of planning, implementation, action, observation, and reflection. The subjects of the study were 30 students of grade 3 of SDN Harapan Jaya XVIII in the even semester of the 2023/2024 school year, consisting of 8 female students and 9 male students, there were 17 students who were not lacking in reading comprehension. This data was collected through observation and interviews. The research instrument is ready to document changes in the learning process and student behavior during the campaign. in cycle I the level of student completion was not as expected. Of the total 30 students, 12 students or 40% of students scored more than 70 and were declared complete, while 18 students (60%) scored less than 70, so they were still classified as incomplete. In this second cycle, the researcher used the drill method which aims to make progress from before, based on the evaluation results showed that there was a significant increase. Of the total 30 students, 17 students (56.7%) obtained a score of ≥ 70 and were declared complete, while 13 students (43.3%) still obtained a score below 70 and were declared incomplete. This increase shows that the drill method applied in cycle II succeeded in improving reading comprehension in students. This study shows that the use of the drill method can significantly improve the reading comprehension of students in grade III of Indonesian Elementary School.